Western Energy Policy : The Case for Competition - Evans, Douglas (London : Macmillan, 1978)
This publication has two parts: Part 1- The pattern of past policies which discusses (a) the role energy policy; (b) international and comparative energy policies and; (c) energy trends in the EEC (European Economic Community). Part 2- The pattern of future policies dealing with (a) German energy policies; (b) British energy policies; (c) United States energy policies and; (d) the prospects of global energy 1985-2000.
Includes index.
Includes bibliographical references: p. [195]-196.
ne 19/04/2018
Loan
Keywords: Energy Policy; Petroleum Industry and Trade